Applications to Integral Equations with Coupled Fixed Point Theorems in Ab-Metric Space: Konchada Ravibabu - Team, Support (Thai Journal of Mathematics, 2018)
In this paper, we establish some results on the existence and uniqueness of coupled common fixed point theorems in partially ordered Ab-metric spaces. Examples have been provided to justify the relevance of the results obtained through the analysis of extant theorem. Further, we also find application to integral equations via fixed point theorems in Ab-metric spaces. Our results generalize and extend the results of Deepak Singh et al. [10].